2021
DOI: 10.1159/000513944
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and Mortality in Patients with Chronic Kidney Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Existing studies suggested conflicting relationships between serum uric acid (SUA) and mortality in CKD patients. The present meta-analysis aimed to determine whether SUA can be a predictor for mortality in CKD cohorts. Method: A systematical search was conducted on PubMed, EMBASE, and The Cochrane Library to identify studies reporting the relationship between SUA level and all-cause and cardiovascular mortality in CKD populations. In addition, random-effects models were adopted to calculate the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…The antioxidant effect of uric acid is protective on the nervous system, intestinal tract, and kidney ( 36 38 ). Some researchers have demonstrated that low uric acid levels are associated with an increased risk of mortality in patients ( 39 , 40 ). Therefore, decreased sex hormones levels and increased uric acid levels in the elderly may be a protective mechanism that needs further exploration in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effect of uric acid is protective on the nervous system, intestinal tract, and kidney ( 36 38 ). Some researchers have demonstrated that low uric acid levels are associated with an increased risk of mortality in patients ( 39 , 40 ). Therefore, decreased sex hormones levels and increased uric acid levels in the elderly may be a protective mechanism that needs further exploration in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid levels are often elevated in patients with CKD due to decreased renal function. Meta-analyses of CKD patients have shown a U-shaped trend between SUA and all-cause mortality ( 17 ), and higher SUA levels are significantly associated with increased risk of cardiovascular mortality ( 18 ). Another meta-analysis of HD patients has shown that high SUA levels are a protective factor for cardiovascular mortality ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have identified SUA as a risk factor for the development of kidney disease in specific populations such as diabetic, non-diabetic, hypertensive, and non-hypertensive populations. 11,[30][31][32][33][34] Given that hyperuricemia can interact with other risk factors, such as metabolic syndrome, diabetes, and hypertension, to accelerate the progression of declining renal function, 33,[35][36][37] prompt identification of high-risk patients is crucial to reduce the burden of CKD. Furthermore, our study revealed a non-linear relationship between SUA levels and the risk of CKD.…”
Section: Discussionmentioning
confidence: 99%